Human Resources Performace And Compatancy Management By Using A Method Of Balanced Scorecard (Case Study: The Experience Of Tanjung Peprak Port-Surabaya) - Abdulmenaam Khamies; M. Ruslin Anwar; Ludfi Djakfar (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2012)
The aim of this paper is to carry out an analysis of the performance tools implemented in the Port Authority of Surabaya city and so, determine whether improvements in management can be achieved if the level of efficiency is established with attainable targets as a consequence of opportune and reliable information in Contraction Management. In this article we analyze how the use of a Balanced Scorecard has helped Tanjung Perak port authority from the Indonesia Port System to implement their strategic Plan. The Port Authorities have become reliant on the Competency Management model as an instrument for strategic planning of human resources and also in the progressive use of Process Management, which aims to meet the objectives established in the Strategic Plan. On this premise, we set out how the abovementioned Port Authority of Tanjung Perak can fulfill specific strategic and operational objectives regarding the efficiency and effectiveness of the services they provide